Legal Implications of The Rejection of The Annual Report of PT Asuransi Jiwasraya (Persero) By Shareholders on The Protection of Customers' Rights to Claims Due - Wibowo, Arif Pratomo Yekti; Sufiarina, Sufiarina (Journal of Law, Politic and Humanities, 2026)
This study aims to analyze the legal implications of the rejection of PT Asuransi Jiwasraya (Persero)'s annual report by shareholders on the protection of customers' rights to due claims. The rejection of the annual report indicates serious problems in corporate governance, including indications of manipulation of financial statements, violations of Good Corporate Governance principles, and the company's inability to fulfill contractual obligations to customers. The research method uses normative and empirical juridical approaches with analytical descriptive specifications, through the analysis of laws and regulations, legal literature, and related documents. The results show that the rejection of the annual report does not remove the company's obligation to pay customer claims, and the directors and commissioners can still be held legally liable. The customer as a creditor has the right to legal protection through a default lawsuit and other legal mechanisms. This research emphasizes the importance of strengthening effective supervision, accountability, and legal protection for customers in the Indonesian insurance industry to ensure legal certainty and public trust.